An Unusual Metastatic Site of a Papillary Thyroid Carcinoma: A Case Report - Cheddadi, Maryam; Sassi, Samia; Boujida, Ismail; Ibelkouchene, Omar; Derqaoui, Sabrine; Mesmoudi, Siham; Jahid, Ahmed; Zouaidia, Fouad; Bernoussi, Zakia; Znati, Kaoutar (Archives of Clinical and Medical Case Reports, 2024)
Metastasis to distant sites in cases of differentiated thyroid cancer is uncommon, with the lungs and bones being the most commonly affected areas. Soft tissue metastases are exceedingly rare. Here, we present an uncommon case of soft tissue metastasis of papillary thyroid cancer to skeletal muscle. This case emphasizes that papillary thyroid carcinoma, while typically following an indolent course, can result in distant metastases to unusual locations.